Is What Scientists Say Always Best? Reflecting on the Role of Perinatal and Infant Experts’ Knowledge in the Cultures, Policies and Practices of Parenthood - Musumeci, Rosy (Cambio. Rivista sulle Trasformazioni Sociali, 2020)
Reviewing recent literature on the topic, this article reflects from a sociological perspective on the influence that perinatal and infant experts’ authority and scientific knowledge have on the cultures, policies and practices of parenthood in contemporary societies. Here the author refers mainly to the heterosexual parenthood and not also to the homogenitorial families that would require a separate discussion. The geographical and social context the author refers to is mainly Italy. After having illustrated the main characteristics of the “expert-led” model in perinatal and infant area and the reasons why it has become increasingly the hegemonic model in the parenting and childrearing cultures and practices, the article presents an overview of the Italian context illustrating data on pregnancy, childbirth, breastfeeding and vaccination. Then it questions about possible research developments in exploring the use that the policy makes of the experts’ knowledge and scientific evidence and the implications of this use. Finally it reflects on the growing diffusion of anti-science movements in perinatal and infant area.